The Role of Zakat, Waqf, and Sharia Financing in Empowering MSMEs: A Systematic Study - Munthe, Syafaruddin (Economic: Journal Economic and Business, 2025)
This article systematically examines the role of zakat, waqf, and Islamic financing in empowering Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The method used is a Systematic Literature Review (SLR) of ten journals published between 2021 and 2025 that are relevant to the topic. The results of the study indicate that these three Islamic social finance instruments have a significant contribution in supporting MSMEs through wealth redistribution mechanisms, the provision of interest-free business capital, training, and mentoring. Zakat functions not only as an obligatory act of worship but also as a source of productive funds for capital and business development. Waqf, especially in the form of cash waqf and innovative instruments such as Cash Waqf Linked Sukuk (CWLS), plays a crucial role in long-term financing for MSMEs. Meanwhile, Islamic financing through the Micro Waqf Bank (BWM) model has successfully provided access to capital to MSMEs underserved by conventional banks. However, challenges such as low public literacy, lack of transparency, and limited synergy between institutions still hamper its optimal utilization. This article emphasizes the need for digitalization of fund management, innovation of social financial instruments, and cross-sector collaboration so that zakat, waqf, and sharia financing can play a greater role in strengthening MSMEs and realizing inclusive economic development.